(untitled) (International Journal of Engineering and Computer Science, 2013)
Brushless Direct Current (BLDC) motors are one of the motor types rapidly gaining popularity. BLDC motors are used in industries such as Appliances, Automotive, Aerospace, Consumer, Medical, Industrial Automation Equipment and Instrumentation. As the name implies, BLDC motors do not use brushes for commutation instead, they are electronically commutated. BLDC motors have many advantages over brushed DC motors and induction motors. A few of these are: Better speed versus torque characteristics, High dynamic response, High efficiency, Long operating life, Noiseless operation, Higher speed ranges. Brushless DC (BLDC) motor simulation can be simply implemented with the required control scheme using specialized simulink built-in tools and block sets such as simpower systems toolbox. But it requires powerful processor requirements, large random access memory and long simulation time. To overcome these drawbacks this paper presents a state space modeling, simulation and control of permanent magnet brushless DC motor. By reading the instantaneous position of the rotor as an output, different variables of the motor can be controlled without the need of any external sensors or position detection techniques. Simulink is utilized with the assistance of MATLAB/Simulink to give a very flexible and reliable simulation. With state space model representation, the motor performance can be analyzed for variation of motor parameters.